Specificity and transfer of lower-body strength: Influence of bilateral or unilateral lower-body resistance training - Appleby, B. B.; Cormack, S. J.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2019)
To examine the development of lower-body strength using either bilateral or unilateral resistance training. Developmental rugby players (n = 33; mean training age = 5.4 ± 2.9 years; 1 repetition maximum [1RM] 90° squat = 178 ± 27 kg) completed an 18-week randomized controlled training design (bilateral group [BIL], n = 13; unilateral group [UNI], n = 10; comparison, n = 10). The 8-week training phase involved 2 lower-body, volume-load matched resistance sessions per week (6-8 sets × 4-8 reps at 45-88% 1RM), differing only in the prescription of a bilateral (back squat) or unilateral (step-up) resistance exercise. Maximum strength was assessed by a randomized order of 1RM back squat and step-up testing and analyzed for within- and between-group differences using effect sizes (ES ± 90% confidence limits [CL]). Both training groups showed practically important improvements in their trained exercise (ES ± 90% CL: BIL = 0.67 ± 0.48; UNI = 0.74 ± 0.38) with transfer to their nontrained resistance exercise (BIL step-up = 0.27 ± 0.39: UNI squat = 0.42 ± 0.39). The difference between groups in adaptation of squat strength was unclear (BIL ES = -0.34 ± 0.55), while the UNI group showed an advantage in step-up training (ES = 0.41 ± 0.36). The results demonstrate that practically important increases in lower-body strength can be achieved using bilateral or unilateral resistance training and development of that strength may be expressed in the movement not trained, supporting the transfer of strength training between exercises of similar joint movements and muscles. Coaches may choose to incorporate unilateral strength training where the prescription of bilateral training may be inhibited.